Global warming potential of building demolition activities - Ghavami Rad, Farzan (2013)
Continuation of urbanization is expected to gradually rise the energy demand for consumption and economic activities. Therefore, a sustainable approach to the development is needed to reduce the consumption of energy. Malaysia has recorded 7.3 tons in carbon dioxide emission per capita in the year 2007. This amount puts Malaysia in the 57th place in the world. This is due to an increase in oil derivatives and gas expenditures in the last decade. Fuel consumption also has a significant role in the demolition of the construction sites as well as their waste disposal. Hence, an increase of demands for demolition has a negative impact on these criteria. Building demolition as a case study for life cycle assessment (LCA) that was conducted for a 18740 m2 floor area, four-storied office, with one story as the top floor, one bridge for connecting the structures and a two-storey basement car park. Menara Tun Razak as its subject, with a projected life span of 29 years; it is located in the commercial area of Kuala Lumpur. Furthermore, a Building Information Modeling (BIM) system is used to determine the accurate quantity of elements and its simulation. The LCA model analyzes the energy use and greenhouse gas (GHG) emissions associated with demolition and waste disposal. The findings show that as much as 225039.021 kilograms of CO2 equivalent of GHGs were released for 15147862 tons of demolition materials where, 97.633 percent or 219713.1 kilogram CO2 equivalent from the amount was carbon dioxide, followed by 1.358 percent or 3056.47 kg CO2 equivalent of methane, 1.008 percent or 2269.188 kilogram CO2 equivalent of dinitrogen monoxide and 0.001 percent or 0.225 kg CO2 equivalent of other gases such as chloroform and ethane. The processes that contributed significantly to the total GHGs emission were mainly from the burning of 57688.8 liters of diesel fuel during demolition. Besides, it is also shown that demolition and waste disposal had a 71.95 percent and 28.04 percent contribution in reinforce concrete framework structure share in producing GHG.